Hábitos motores e identidade pessoal - Bissoli, Ana Paula Talin (Editora Oficina Universitária, 2021)
The central objective of this work is to analyze, from a philosophical-interdisciplinary point of view, possible contributions of motor habits in the constitution of personal identity. Initially, the authors problematize the approach of mechanistic theories that consider the body as a totality decomposable into its parts. In this approach, the motor habituation process would only result from processes directed by neuronal maturation. In contrast, from a conception of the person's systemic identity, based on the perspective of dynamic systems and embodied and situated cognition, they seek to show that the person's body, as a complex dynamic organization, and motor activities in general, are fundamental for the instantiation and development of motor habits that constitute their identity. The book focuses especially, from the conception of abductive reasoning proposed by Charles Sanders Peirce, the possible role of motor abductive processes in the constitution of the person's motor identity.